The Existence of Batu Bolong Temple in Supporting West Batu Layar as A Marine Tourism Village On Lombok Island, Indonesia - Prayitno, Joko (Jurnal Penelitian Agama Hindu, 2024)
Batu Bolong Temple is a Hindu tourist destination in Batulayar Barat Village, Lombok, Indonesia. Batu Bolong Temple is located in a fairly well-known coastal tourist area on Lombok Island, namely the Senggigi Beach area. The dynamics of the development of Batu Bolong Temple gradually influenced and developed following the conditions of tourism development on Lombok Island. This study aims to examine the existence of Batu Bolong Temple in supporting Batu Layar Barat as a marine tourism village on Lombok Island. This study uses a qualitative method, with interview techniques with several people, tourists, traders, and temple managers, as well as conducting direct observations at the location and literature studies. The study results show that this temple is not only used by Hindus but is also visited by tourists with basic purposes, reasons, and argument factors. The tourist attraction of Batu Bolong Temple is in the form of interesting tourist objects and attractions for tourists to enjoy. The temple manager carries out good management in maintaining the existence of Batu Bolong Temple. Batu Bolong Temple is relevant in supporting Batulayar Barat as a marine tourism village in terms of location, promotion, price, supporting facilities, transportation facilities, infrastructure, and management. Based on the results of the analysis and discussion of the findings, it is confirmed that the existence of Batu Bolong Temple can support the development of Batu Layar as a marine tourism village.